The Factors Influencing on Consumption of Palm Cooking Oil in Indonesia - Ermy Teti; Sakti Hutabarat; Asriati Nofionna (Economic Journal of Emerging Markets, 2009)
Cooking oil is one of the most sensitive basic needs in Indonesia. The aims of the researchare to analyze factors influencing consumption of cooking oil, the cooking oil price, and theCrude Palm Oil price in Indonesia. Using simultaneous equation model, the study show thatpalm cooking oil consumption is significantly affected by domestic palm cooking oil priceand number of population. Whilst palm cooking oil price is significantly influenced by thecooking palm oil production and the domestic Crude Palm Oil price. Finally, the domesticCrude Palm Oil is significantly affected by international Crude Palm Oil price.Keywords: consumption, cooking oil price, crude palm oil price and cooking oil